“PLEASE DON’T TREAT ME LIKE A SERVANT. I DO HAVE MY RIGHTS”: INDONESIAN MIGRANT DOMESTIC WORKERS (IMDWS) WROTE BACK IN FAMILIAR STRANGERS (2018) - Ririn Kurnia Trisnawati (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Facilitated by The Voice of Singapore’s Invisible Hands, a non-profit organization (NPO) that promotes the rights and welfare of migrant workers in Singapore through literary works on Facebook, some Indonesian Migrant Domestic Workers (IMDWs) in Singapore such as Seruni, Fadillah, et. al., to name a few, have been able to publish their poems and short stories in an anthology entitled “Familiar Strangers” (2018). To add to the current studies of literary works written by migrant workers that are about home and family as well as migratory experience of exile, loneliness, alienation, and isolation, the present study offers a different perspective of IMDW’s migratory experience working in Singapore that is depicted in the six selected poems through the postcolonial lens. Accordingly, it examines the migrant workers’ salient migratory experience of working in Singapore that, I argue, conveys voices of renegotiation for better IMDWs’ position as domestic workers and thus challenges certain stereotypes about them. The voice of renegotiation is expressed by vocalizing steadfastness and courage where subversion and confrontation against the dehumanization they oftentimes encounter can also be observed. These IMDWs through their poems are seen as a countering narrative about Indonesian domestic workers, and the notion of writing back is then solidly founded.